Surveillance and Control of Fiscal Consolidation on a Supranational Level - Bas van Aarle (WWWforEurope, 2013)
Strengthening budgetary surveillance and coordination of budgetary policy measures in the EU is of vital importance for economic stability and growth. The decentralised decision making structure in most areas of budgetary policies, requires the need to balance national and common objectives; clearly also given the context of highly integrated goods-, labour-, and financial markets that lead to significant interdependencies and spillovers, as e.g. the recent financial crisis and economic slowdown demonstrate. We analyse the progress that is underway in the current budgetary governance framework in the EU -including the recent new instruments in the form of the Macroeconomic Imbalance procedure, the European Semester, Stability Bonds, the European Financial Stability Facility, Euro+ Pact and Europe 2020. This paper surveys supranational governance in the EU, and the coordination of national policies, including concepts of fiscal federalism, multi-level governance and open coordination methods, control and systems methods and macro-finance. We relate this exercise to the current context of budgetary stress in the aftermath of the global financial crisis and economic slowdown which has strongly impacted on the economies and public finances of the Member States. We consider financial market conditions that have exerted a particular strong influence in the European debt crisis and evaluate specifically the merits and risks relating to proposals for the introduction of Eurobonds. We conclude by formulating the policy recommendations on streamlining EU economic and budgetary governance that could be drawn from our analysis.
Keywords: C70; D70; E30; E60; H60; H70; H80; 330; Academic research; challenges for welfare system; competitiveness; economic strategy; EU integration; European economic policy; European governance; European Monetary Union; Institutional reforms; acroeconomic disequilibria; multi-level governance